(untitled) (Journal of the Bangladesh Agricultural University, 2017)
Organic manures as a source of plant nutrients for the cultivation of field crops has received worldwide attention due to rising costs, rapid nutrient loss and adverse environmental impacts from inorganic fertilizers. A pot experiment was conducted in the net house of the Department of Agricultural Chemistry, BangladeshAgriculturalUniversity, Mymensingh to observe the effects of cow dung on growth, yield of stevia along with post-harvest fertility status of soil. Four treatments of CD viz. 0, 5, 7.5 and 10 t ha–1 in two contrasting soils (acid and non-calcareous) were examined following Completely Randomized Design (CRD) with three replications. Growth and yield attributes increased significantly with the advancement of growth period (60 DAP) and increased rate of CD up to 10 t ha–1. An overall performance of non-calcareous soil was better than acid soil. In non-calcareous soil, the leaf biomass yield was increased by 275% whereas in acid soil it was 268% over control. The acidity of both soils significantly decreased with the increased rate of CD. All essential plant nutrients viz. total N, available P exchangeable K, Ca, Mg, available S, Zn, B and organic matter content of soil were significantly increased with the increased levels of CD up to its highest dose (CD @ 10 t ha–1) in both soils. Thus from the findings of the present research work it can be concluded that for getting optimum leaf biomass yield of stevia along with fertility of both soils CD should be applied @ 10 t ha–1 J. Bangladesh Agril. Univ. 15(2): 206-211, December 2017